Bhutan Urban Policy Notes - World Bank Group (World Bank, Washington, DC, 2019)
Despite its small absolute size and population, Bhutan is the most rapidly urbanizing country in South Asia. This urbanization has coincided with strong economic growth as the country shifts toward an economy based on contributions from manufacturing and services clustered in and around cities. Across the country, there has also been remarkable convergence in terms of infrastructure coverage, however the quality of services, as well as poverty and happiness levels vary widely between urban and rural areas. As detailed in the 12 Five Year Plan, Bhutan aims to balance sustainable development with decentralization for greater administrative authority to local governments. Yet there remain significant challenges to local governments in managing urban expansion, forces of congestion and pollution and ensuring affordability of housing and equity of access to services. Each of these factors can reduce the livability, resilience and potential for economic competitiveness in Bhutan's growing cities. Based on consultations with the government, the policy notes provide a current assessment of and policy and investment recommendations for four critical areas: i) regional development, ii) municipal governance and finance, iii) urban resilience and iv) affordable housing.